2021
DOI: 10.1108/oir-03-2021-0133
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of unauthorized use of books: readers, authors, and publishers' perspective

Abstract: PurposeThe current study aims to identify and explore causes and consequences of unauthorized use of books from readers', publishers', and authors' points of view. The case of Lithuania also assessed, especially historical background (banned alphabet, book smuggling, theft as the social norm in Soviet times) of the country.Design/methodology/approachAiming for more understanding why readers, authors and publishers are using or not using technology for unauthorized access of books, technology acceptance model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…There needs to be more that existing regulations to reduce the demand for and supply of pirated books online. Referring to Lithuania, Gudinavičius and Grigas (2022) revealed that perpetrators of pirated book distribution are predominantly illegal website users with four channels: online bookstores, libraries, subscription service platforms, and academic online bookstores (Gudinavičius & Grigas, 2022). Another study explained that publishers' choice not to print e-books or make them available in minimal quantities further boosts book piracy statistics in these channels (Gudinavičius & Grigas, 2022).…”
Section: Online Sale Of Pirated Books From a Legal And Moral Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…There needs to be more that existing regulations to reduce the demand for and supply of pirated books online. Referring to Lithuania, Gudinavičius and Grigas (2022) revealed that perpetrators of pirated book distribution are predominantly illegal website users with four channels: online bookstores, libraries, subscription service platforms, and academic online bookstores (Gudinavičius & Grigas, 2022). Another study explained that publishers' choice not to print e-books or make them available in minimal quantities further boosts book piracy statistics in these channels (Gudinavičius & Grigas, 2022).…”
Section: Online Sale Of Pirated Books From a Legal And Moral Perspectivementioning
confidence: 99%
“…Referring to Lithuania, Gudinavičius and Grigas (2022) revealed that perpetrators of pirated book distribution are predominantly illegal website users with four channels: online bookstores, libraries, subscription service platforms, and academic online bookstores (Gudinavičius & Grigas, 2022). Another study explained that publishers' choice not to print e-books or make them available in minimal quantities further boosts book piracy statistics in these channels (Gudinavičius & Grigas, 2022). In Indonesia, Fitirasih et al ( 2019) also revealed that students are motivated to use pirated books because of the benefits they receive, and they have no fear of sanctions for using them (Fitriasih et al, 2019).…”
Section: Online Sale Of Pirated Books From a Legal And Moral Perspectivementioning
confidence: 99%